Impact of co-fermenting modified camel milk using yogurt starter culture and Limosilactobacillus fermentum on the quality of quinoa-supplemented fermented milk products - Alsadun, Amjad F. A.; Sakr, Sally S.; Ali, Asmahan A.; Alsaleem, Khalid A.; Aladhadh, Mohammed; Aljutaily, Thamer; Almujaydil, Mona S.; Alayouni, Raed; Hassan, Ateteallah; Barakat, Hassan; Hassan, Mohamed F. Y. (Frontiers in Nutrition, 2025)
IntroductionFermented camel milk represents a functional dairy product of significant nutritional and pro-biotic value, yet optimization of its coagulation properties and bioactive compound content remains under-studied.MethodsThis study investigated the enhancement of coagulation quality in fermented camel milk by in-corporating whey protein isolate (WPI) and trisodium citrate (TSC) to facilitate improved acid coagulation. Additionally, the research examines the effects of quinoa seed preparations on the quality of the resultant products. In the preliminary phase, camel milk was supplemented with either 1.5% or 2% WPI in conjunction with TSC at a concentration of 30 mmol L−1, analyzing the resultant fermentation characteristics.ResultsCamel milk with 2% WPI and TSC significantly expedited acidification and reduced fermentation time. Furthermore, this formulation enhanced gel formation and viscosity during fermentation with the yoghurt starter culture (YC–381) and Limosilactobacillus fermentum (B–1932). Due to these promising outcomes, this formulation was chosen for the subsequent study phase. In the second phase, camel milk that had undergone pre-modification before fermentation received 1–3% additions of quinoa sprout flour (QSF) or freeze-dried aqueous quinoa extract (AQE). The blended fermented products were assessed for their physicochemical, microbiological, and antioxidant properties, as well as sensory and microstructural characteristics over a 15-day storage period at 4 ± 1 °C. Notably, all quinoa preparations, particularly the 3% AQE supplementation, sig-nificantly accelerated acidification, improved water-holding capacity, and increased antioxidant activity in the blended samples. The microstructural analysis revealed that samples containing 3% AQE developed a gel network characterized by reduced pore size and enhanced porosity. In addition, incorporating AQE facilitated greater viability of starter cultures compared to QSF, likely attributed to its superior nutrient availability.DiscussionThe co-fermentation of modified camel milk with a yoghurt starter culture and L. fermentum, in combination with quinoa supplementation, enhanced fermentation efficiency, functional properties, and pro-biotic viability.